Strategic Interplays: Assessing the Global Impact of Growth, Tax Planning, and Earnings Management [Interaksi Strategis: Menilai Dampak Global dari Pertumbuhan, Perencanaan Pajak, dan Manajemen Laba - Arum, Wahyu; Sriyono, Sriyono (Indonesian Journal Publisher, 2023)
This study examines the influence of company growth, deferred tax expense, and tax planning on earnings management, using financial performance as a moderating variable in the basic and chemical industries sector at the Indonesian Stock Exchange during 2018-2020. Utilizing a quantitative approach with purposive sampling, the research analyzed data from 48 companies, resulting in 144 data points. The Moderated Regression Analysis technique, supported by the Eviews software, was employed for data analysis. The findings indicate that deferred tax expense significantly affects earnings management, whereas company growth and tax planning do not show significant effects. Interestingly, financial performance does not moderate the impact of company growth and deferred tax expense on earnings management but does moderate the effect of tax planning on earnings management. These results highlight the need for companies to consider the complexities of financial tactics and their implications on earnings management, offering valuable insights for future researchers, corporate management, and investors regarding governance and ethical management practices.